Linguistic competence in tertiary-level instruction in English and its relevance for student mobility - Kovačić, Andreja (Array, 2009)
Abstract: Student and teacher mobility are important aspects of education within the Bologna Process. Overcoming the language barrier is a precondition for following and providing instruction in a foreign language. A survey was conducted among first-year undergraduate students to determine their readiness for instruction in English. The survey results show the respondent profile, their assessment of instruction within an English language course, using other ways of acquiring knowledge and self-assessment of their command of English. The students' self-assessment of motivation for learning English and its relevance for their profession are presented along with students' interest in other courses offered in English. It turns out that, regardless of a satisfactory level of self-assesed competence in English and motivation for learning English, students are not willing to enroll in the offered study courses in English.